Kampo Formula-Pattern Models: The Development of 13 New Clinically Useful Standard Abdominal Pattern Models in the Fukushin Simulator - Yakubo, Shuji; Baba, Masaki; Odaguchi, Hiroshi; Wakasugi, Akino; Sekine, Mariko; Hanawa, Toshihiko; Mitsuma, Tadamichi; Namiki, Takao; Arai, Makoto; Muramatsu, Shin-Ichi; Shimada, Yutaka; Shibahara, Naotoshi (Frontiers in Pharmacology, 2022)
Aim: In Kampo medicine, there exists an important system of diagnosis called Fukushin, or abdominal diagnosis or palpation. By applying pressure to the abdomen of the patient, the physician can gain important information on the patient’s physical state and use those indications to choose a suitable Kampo formulation. We have previously developed a Fukushin simulator, a teaching tool that reproduces the important abdominal patterns that doctors will encounter in clinical practice and that has received favourable feedback for students and practitioners. In order to make diagnosis and prescription easier, it is desirable to have matched formula–pattern pairings. The present study aims to develop such pairings. Methods: With the previously developed models as a foundation, in the present study the production team (two members) used materials such as urethane foam and silicone rubber to build an additional 13 standard abdominal pattern models matched to Kampo herbal formulas commonly used by practitioners in Japan. Subsequently, the evaluation team (the remaining10 authors) investigated the viability of these models. Results: The evaluation team determined that abdominal pattern models matched to the following typical Kampo formulas were created successfully: Dai-saiko-To (大柴胡湯), Dai-joki-To (大承気湯), Shigyaku-San (四逆散), Saiko-ka-ryukotsu-borei-To (柴胡加竜骨牡蛎湯), Keishi-bukuryo-Gan (桂枝茯苓丸), Hachimi-jio-Gan (八味地黄丸), Hange-shashin-To (半夏瀉心湯), Sho-saiko-To (小柴胡湯), Hochu-ekki-To (補中益気湯), Sho-kenchu-To(小建中湯), Toki-shakuyaku-San (当帰芍薬散), Ninjin-To (人参湯), and Dai-kenchu-To (大建中湯). Conclusion: We suggest that these new formula-pattern models can make an important contribution to the standardization of abdominal diagnosis and prescription and to Kampo education.